2012
DOI: 10.3390/ijms131012584
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Anti-pathogenic Agents Based on Core/Shell Nanostructures and 2-((4-Ethylphenoxy)ethyl)-N-(substituted-phenylcarbamothioyl)-benzamides

Abstract: The purpose of this study was to design a new nanosystem for catheter surface functionalization with an improved resistance to Staphylococcus aureus ATCC 25923 and Pseudomonas aeruginosa ATCC 27853 colonization and subsequent biofilm development. New 2-((4-ethylphenoxy)methyl)-N-(substituted-phenylcarbamothioyl)-benzamides were synthesized and used for coating a core/shell nanostructure. Their chemical structures were elucidated by NMR, IR and elemental analysis, being in agreement with the proposed ones. Fe3O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…We have suggested before the efficiency of nanosystem-vectored essential oil strategy [23]. The Fe 3 O 4 /C 12 nanoparticles seem not to be cytotoxic on the HEp2 cell line, which is a great advantage for the in vivo use of these nanostructure systems for biomedical applications with minor risks of the occurrence of side effects [48]. …”
Section: Resultsmentioning
confidence: 99%
“…We have suggested before the efficiency of nanosystem-vectored essential oil strategy [23]. The Fe 3 O 4 /C 12 nanoparticles seem not to be cytotoxic on the HEp2 cell line, which is a great advantage for the in vivo use of these nanostructure systems for biomedical applications with minor risks of the occurrence of side effects [48]. …”
Section: Resultsmentioning
confidence: 99%
“…The purpose of this study was to design a new nanosystem for catheter surface functionalization with improved resistance to S. aureus and P. aeruginosa colonization and subsequent biofilm development. Viable cell counts and SEM examination demonstrated that the nano-coated surfaces inhibited both the initial attachment and biofilm development of S. aureus and P. aeruginosa on the functionalized catheter surfaces (Limban et al, 2012).…”
Section: Magnetite Nanoparticles Used To Control Microorganisms Attacmentioning
confidence: 99%
“…The analysis showed that the tested nanobiosystem exhibited an intensive antibiofilm effect, as demonstrated by a low number of yeast cells that adhered to the coated surface (Anghel et al, 2012b). Limban et al (2012) reported the synthesis of new 2-((4-ethylphenoxy)methyl)-N-(substituted-phenylcarbamothioyl)-benzamides and their usage as coatings for a core/shell nanostructure. The purpose of this study was to design a new nanosystem for catheter surface functionalization with improved resistance to S. aureus and P. aeruginosa colonization and subsequent biofilm development.…”
Section: Magnetite Nanoparticles Used To Control Microorganisms Attacmentioning
confidence: 99%
“…The assessment of the complexes influence on the microbial ability to colonize an inert substratum was performed by the microtiter method, following previously described protocols [34][35][36][37] …”
Section: Antimicrobial Activity Assaysmentioning
confidence: 99%